Pressing Replay on a Life - Pence, William (Ars Medica, 2015)
I watched my daughter lean forward to hear Dr. W. ask, "What is your biggest fear?" Dr. W.'s first name was Hope, a suitable name for a young doctor, not yet forty, in the specialized practice of caring for the dying. Hope spoke warmly but with clarity and volume, aware that the Cisplatin chemotherapy had damaged Molly's hearing.